2010
DOI: 10.1007/s00232-010-9331-9
|View full text |Cite
|
Sign up to set email alerts
|

UT-B1 Mediates Transepithelial Urea Flux in the Rat Gastrointestinal Tract

Abstract: The process of urea nitrogen salvaging plays a vital role in the symbiotic relationship between mammals and their intestinal bacteria. The first step in this process requires the movement of urea from the mammalian bloodstream into the gastrointestinal tract lumen via specialized proteins known as facilitative urea transporters. In this study, we examined both transepithelial urea fluxes and urea transporter protein abundance along the length of the rat gastrointestinal tract. Urea flux experiments that used r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…This confirms that UT-B2 transporter protein is abundant in papillae throughout the bovine rumen. In contrast, the 30-35 kDa signals expected for UT-B1 protein (Collins et al 2010(Collins et al , 2011Walpole et al 2014) were not detected by hUTBc19, in agreement with the weak UT-B1 transcript expression observed in RT-PCR experiments (Figs. 1, 2).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This confirms that UT-B2 transporter protein is abundant in papillae throughout the bovine rumen. In contrast, the 30-35 kDa signals expected for UT-B1 protein (Collins et al 2010(Collins et al , 2011Walpole et al 2014) were not detected by hUTBc19, in agreement with the weak UT-B1 transcript expression observed in RT-PCR experiments (Figs. 1, 2).…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that UT-B protein is present all along the gastrointestinal tract of both cows (Dix et al 2013) and sheep (Ludden et al 2009), in contrast to observations in rats (Collins et al 2011). In agreement with predictions based on the known regulators of urea transport, the observed ruminant UT-B abundance pattern appeared to be rumen [ small intestine & colon (Dix et al 2013).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Details of the protocol are given in University but also at UCD using plasma membrane vesicle samples which had been brought back (flight back from Hungary) on dry ice. The Western analyses system at UCD was the same one as described by Collins et al (2011). Red TR / Naphthol AS-MX Tablets (Sigma) following the instructions of the manufacturer.…”
Section: Dehydration and Embeddingmentioning
confidence: 99%